Quantifying anthropogenic wolf mortality in relation to hunting regulations and landscape attributes across North America. Issue 5 (20th May 2022) - Hill, Jacob E.; Boone, Hailey M.; Gantchoff, Mariela G.; Kautz, Todd M.; Kellner, Kenneth F.; Orning, Elizabeth K.; Parchizadeh, Jamshid; Petroelje, Tyler R.; Wehr, Nathaniel H.; Finnegan, Shannon P.; Fowler, Nicholas L.; Lutto, Ashley L.; et al.
Abstract: Understanding the types and magnitude of human‐caused mortality is essential for maintaining viable large carnivore populations. We used a database of cause‐specific mortality to examine how hunting regulations and landscape configurations influenced human‐caused mortality of North American gray wolves ( Canis lupus ). Our dataset included 21 studies that monitored the fates of 3564 wolves and reported 1442 mortalities. Human‐caused mortality accounted for 61% of mortality overall, with 23% due to illegal harvest, 16% due to legal harvest, and 12% the result of management removal. The overall proportion of anthropogenic wolf mortality was lowest in areas with an open hunting season compared to areas with a closed hunting season or mixed hunting regulations, suggesting that harvest mortality was neither fully additive nor compensatory. Proportion of mortality from management removal was reduced in areas with an open hunting season, suggesting that legal harvest may reduce human‐wolf conflicts or alternatively that areas with legal harvest have less potential for management removals (e.g., less livestock depredation). Proportion of natural habitat was negatively correlated with the proportion of anthropogenic and illegal harvest mortality. Additionally, the proportion of mortality due to illegal harvest increased with greater natural habitat fragmentation. The observed association between large patches of natural habitat and reductions in several sources of anthropogenic wolf mortality reiterate the importance of habitat preservation to maintain wolf populations. Furthermore, effective management of wolf populations via implementation of harvest may reduce conflict with humans. Effective wolf conservation will depend on holistic strategies that integrate ecological and socioeconomic factors to facilitate their long‐term coexistence with humans. Abstract : Wolf mortality from management removal was reduced when harvest was legal, suggesting that legal harvest may reduce human–wolf conflicts. Anthropogenic mortality of wolves was greatest in landscapes with less natural habitat.